CRISPR-based knockout and base editing confirm the role of MYRF in heart development and congenital heart disease - Doering, Lino; Cornean, Alex; Thumberger, Thomas; Benjaminsen, Jørgen; Wittbrodt, Beate; Kellner, Tanja; Hammouda, Omar T.; Gorenflo, Matthias; Wittbrodt, Joachim; Gierten, Jakob (Disease models & mechanisms, 2023)
High-throughput DNA sequencing studies increasingly associate DNA variants with congenital heart disease (CHD). However, functional modeling is a crucial prerequisite for translating genomic data into clinical care. We used CRISPR-Cas9-mediated targeting of 12 candidate genes in the vertebrate model medaka (Oryzias latipes), five of which displayed a novel cardiovascular phenotype spectrum in F0 (crispants): mapre2, smg7, cdc42bpab, ankrd11 and myrf, encoding a transcription factor recently linked to cardiac-urogenital syndrome. Our myrf mutant line showed particularly prominent embryonic cardiac defects recapitulating phenotypes of pediatric patients, including hypoplastic ventricle. Mimicking human mutations, we edited three sites to generate specific myrf single-nucleotide variants via cytosine and adenine base editors. The Glu749Lys missense mutation in the conserved intramolecular chaperon autocleavage domain fully recapitulated the characteristic myrf mutant phenotype with high penetrance, underlining the crucial function of this protein domain. The efficiency and scalability of base editing to model specific point mutations accelerate gene validation studies and the generation of human-relevant disease models.
Online veröffentlicht: 16. August 2023
Gesehen am 23.11.2023